Corporate Social responsibility in the petrochemical industry: Exploring current trends in social and environmental disclosure - Lei, Juan (2006)
Current trends indicate that we are entering a new phase of corporate responsibility reporting that more emphasis is paid on social responsibility, but significant variation still remains in the maturity of reporting content and styles in industries, and even in the same industry. This study explores the current trend of corporate social and environmental reporting in petrochemical industry. It offers a detailed review of the development of corporate social responsibility reporting, and of the driving factors of the disclosure in petrochemical industry. Content analysis method is employed to analyze the annual reports, separate social and environmental reports, and corporate websites of the world's 10 largest petrochemical companies. The results suggest that companies still disclose social and environmental performance in annual reports, but the disclosure amount and levels are not anticipated to experience significant increase. Stand-alone social and environmental reports are becoming major media of disclosing corporate responsibilities, and there is evidence of increasing sophistication and integration in these reports. Although social and environmental reporting is more prevalent among larger corporations, marked regional variations still exist, and there is considerable variation in reporting methods and reporting styles within petrochemical industry.